Design and Evaluation of a Conversational Agent for Facilitating Idea Generation in Organizational Innovation Processes - Mathis Poser; Gerrit C. Küstermann; Navid Tavanapour; Eva A. C. Bittner (Information Systems Frontiers, 2022)
Large numbers of incomplete, unclear, and unspecific submissions on idea platforms hinder organizations to exploit the full potential of open innovation initiatives as idea selection is cumbersome. In a design science research project, we develop a design for a conversational agent (CA) based on artificial intelligence to facilitate contributors in generating elaborate ideas on idea platforms where human facilitation is not scalable. We derive prescriptive design knowledge in the form of design principles, instantiate, and evaluate the CA in two successive evaluation episodes. The design principles contribute to the current research stream on automated facilitation and can guide providers of idea platforms to enhance idea generation and subsequent idea selection processes. Results indicate that CA-based facilitation is engaging for contributors and yields well-structured and elaborated ideas.
Keywords: 000; Conversational Agent; Facilitation; Human-AI Interaction; Idea Generation; Open Innovation